2021
DOI: 10.1039/d0cp05180b
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chemical interaction of molybdenum and silicon in a Mo/Si multilayer structure by the formation of intermediate compounds

Abstract: In the present study, the formation of intermediate compounds in the Mo/Si multilayer was realized by the introduction of barrier layers at the interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The Mo3d spectrum contained two main doublets described by the 3d 5/2 and 3d 3/2 states. Peaks corresponding to binding energies of 227.6 and 230.8 eV indicate that molybdenum is chemically bonded to silicon [36,37]. Low-intensity peaks at positions 228.8 and 232.3 eV correspond to Mo-O bonds [38].…”
Section: Gas Flowmentioning
confidence: 99%
“…The Mo3d spectrum contained two main doublets described by the 3d 5/2 and 3d 3/2 states. Peaks corresponding to binding energies of 227.6 and 230.8 eV indicate that molybdenum is chemically bonded to silicon [36,37]. Low-intensity peaks at positions 228.8 and 232.3 eV correspond to Mo-O bonds [38].…”
Section: Gas Flowmentioning
confidence: 99%
“…This effect can be associated with For all coatings, the Mo3d spectrum contained two main doublets, described by the 3d 5/2 and 3d 3/2 states. Peaks corresponding to binding energies of 227.6 and 230.8 eV indicated that molybdenum was chemically bonded to silicon [32,33]. Low-intensity peaks at positions 228 and 231.4 eV corresponded to Mo-O bonds [34].…”
Section: Oxidation Resistancementioning
confidence: 99%